From Patriarchy to Heteroarchy in Islamic Family Law: Conceptualization of Equal Partnerships Between Husband and Wife - Hurnawijaya, Hurnawijaya; Muhtolib, Muhtolib (Tasyri' : Journal of Islamic Law, 2026)
The relationship between men and women in Islamic family law has often been understood through a patriarchal framework that positions men as the dominant party in the family structure. This understanding often gives rise to legal and social practices that have the potential to obscure the principles of justice and partnership that are the fundamental spirit of Islamic teachings. This article aims to analyze and reconstruct the husband-wife relationship in Islamic family law through a heterarchical approach, as an alternative to the patriarchal paradigm. This research uses qualitative methods with a normative-conceptual approach, through an analysis of classical and contemporary Islamic legal sources, as well as a literature review on gender relations theory. The results of the study indicate that the concept of heterarchy—which emphasizes non-hierarchical and complementary relationships—is consistent with the basic principles of Islamic family law, such as justice ('adl), partnership (musyārakah), and mutual protection (wilāyah mutabādilah). This article argues that the husband-wife relationship in Islam is not superior-inferior, but rather functional and contextual, depending on the capabilities and agreements of each party. Thus, the heterarchical approach can be a relevant conceptual framework in efforts to reform Islamic family law to make it more responsive to contemporary social dynamics without relinquishing its normative foundation.